Aesthetics Innovation and Practice of Urban Bridge Design. Issue 4 (2nd October 2021) - Han, Zhenyong
Abstract: The objective of a bridge design is to produce a safe bridge that satisfies all functional requirements with a cost that is acceptable by the owners. However, with accelerated development of people's aesthetic awareness, the design of urban bridges is gradually developing towards novelty, harmony, and customization. The most critical issue in constructing an aesthetically pleasing bridge is that there is no such rule to conceive of the most perfect or elegant design. In recent decades, a large number of bridges have been built on the Haihe River in Tianjin, China. This paper focuses on the introduction and implementation of innovative aesthetics design for urban bridges in this city. The design of new bridges on the Haihe River adheres to the people-oriented conception, and to the successful combination of aesthetics and functional design specifications. Complementary scientific strategies are implemented during the reconstruction of old bridges on the river to protect the cultural relics and preserve the history. The overall design conception in this paper is the harmony of mechanics and aesthetics as well as the harmony of bridges and its surrounding environment. Also, the designers and constructors follow the rules of inheriting historical emotions and human emotions. Several novel bridge cases are employed in the paper to demonstrate the design conception.